Cancer-Germline Antigen Expression Discriminates Clinical Outcome to CTLA-4 Blockade - Shukla, Sachet A.; Bachireddy, Pavan; Schilling, Bastian; Galonska, Christina; Zhan, Qian; Bango, Clyde; Langer, Rupert; Lee, Patrick C.; Gusenleitner, Daniel; Keskin, Derin B.; Babadi, Mehrtash; Mohammad, Arman; et al. (Cell, 2018)
CTLA-4 immune checkpoint blockade is clinically effective in a subset of patients with metastatic melanoma. We identify a subcluster of MAGE-A cancer-germline antigens, located within a narrow 75 kb region of chromosome Xq28, that predicts resistance uniquely to blockade of CTLA-4, but not PD-1. We validate this gene expression signature in an independent anti-CTLA-4-treated cohort and show its specificity to the CTLA-4 pathway with two independent anti-PD-1-treated cohorts. Autophagy, a process critical for optimal anti-cancer immunity, has previously been shown to be suppressed by the MAGE-TRIM28 ubiquitin ligase in vitro. We now show that the expression of the key autophagosome component LC3B and other activators of autophagy are negatively associated with MAGE-A protein levels in human melanomas, including samples from patients with resistance to CTLA-4 blockade. Our findings implicate autophagy suppression in resistance to CTLA-4 blockade in melanoma, suggesting exploitation of autophagy induction for potential therapeutic synergy with CTLA-4 inhibitors. [Display omitted] •Increased expression of a MAGE-A subcluster predicts resistance to CTLA-4 blockade•This MAGE-A subcluster marks a distinct, epigenetically defined subset of melanomas•This gene signature is specific to resistance to CTLA-4, but not PD-1, blockade•Autophagy is implicated in clinical resistance to CTLA-4 blockade Increased expression of a subcluster of MAGE-A cancer-germline antigens predicts resistance specific to CTLA-4, but not PD-1, blockade, and its association with autophagy suppression implicates the role of autophagy in regulating primary resistance to anti-CTLA-4 therapy in melanoma patients.